Towards a new infrastructure in the battle of gender equality? – a recognition theoretical analysis of the public tariff negotiations in 2008 - Gleerup, Janne (Tidsskrift for Arbejdsliv, 2010)
The starting point of the article is a number of empirical studies on what characterizes the creation of identity and meaning among employees in the Danish public care sector. The background for this analysis was that the Danish care sector suffers from crises of recruitment and retention, as well as high absenteeism due to sickness. The sector has through out the last decade been exposed to massive topdown restructuring, changing the work and the work conditions. In general, research shows, that employees experience a poor working atmosphere and loss of infl uence in their daily work. My analysis shows, however, that the problems care workers experience relate not only to the process of modernization. Frustrations are also embedded in underlying societal and genderrelated confl icts - as it became obvious in the bargaining process in 2008 where the care working along with other ‘female professions’ chose to strike for wage increase. In the article I contextualize the results of my phenomenological analysis of the care workers creation of identity meaning in a critical theoretical perspective as used by Axel Honneth. Viewing the strike as a ‘struggle of recognition’ I analyze the broader societal ‘moral grammar’ framing the care workers fi ght for wage increases. Additionally perspectivized by Nancy Fraser and Charles Taylor it appears that the so called Danish model is gendered in ways that limit the care workers and their union in the effort of improving equality as regards pay and recognition of reproductive work. My results show how some of the central dimensions in the care workers´ process of meaning creation, owing to the various changing strategies on the part of their union, FOA, during the strike came to be exposed and politicized in new ways. How ever trade unions are facing new challenges if they want to support the care workers search of a ‘new justice’ in the future.